2007
DOI: 10.1073/pnas.0610251104
|View full text |Cite|
|
Sign up to set email alerts
|

The hallmark of AGC kinase functional divergence is its C-terminal tail, a cis-acting regulatory module

Abstract: The catalytic activities of eukaryotic protein kinases (EPKs) are regulated by movement of the C-helix, movement of the N and C lobes upon ATP binding, and movement of the activation loop upon phosphorylation. Statistical analysis of the selective constraints associated with AGC kinase functional divergence reveals conserved interactions between these regulatory regions and three regions of the C-terminal tail (C-tail): the N-lobe tether (NLT), the active-site tether (AST), and the C-lobe tether (CLT). The NLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
280
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 211 publications
(289 citation statements)
references
References 51 publications
8
280
0
1
Order By: Relevance
“…The active site tether (AST) that links these two segments is dynamic and locks the kinase into a closed conformation in the presence of nucleotides (Fig. S3) (23,25,26). The FDDY motif (residues 327-330) is the signature motif of the AST and interacts directly with ATP.…”
Section: Resultsmentioning
confidence: 99%
“…The active site tether (AST) that links these two segments is dynamic and locks the kinase into a closed conformation in the presence of nucleotides (Fig. S3) (23,25,26). The FDDY motif (residues 327-330) is the signature motif of the AST and interacts directly with ATP.…”
Section: Resultsmentioning
confidence: 99%
“…This loop is the only part of the N-lobe that is firmly anchored to the C-lobe and serves as a hinge point for C-helix movement (26). More recent studies have suggested a role for this motif in kinase regulation (27), because variations within this loop appear to favor alternative modes of C-helix positioning (21,28). Mutations at this site produce severe (29,30) and/or dominant-negative effects (31).…”
Section: N-lobementioning
confidence: 99%
“…In Cdk2, for instance, the K92 equivalent (I52) directly interacts with cyclin A, which is a key regulator of Cdk2 activity (20). Likewise, in AGC kinases, K92 positions the C-terminal tail, which serves as a cis-regulatory element (21). Moreover, K92 is strategically located relative to the kinase conserved E91, which positions the ATP by forming a salt bridge interaction with K72.…”
Section: N-lobementioning
confidence: 99%
“…The C-tail is anchored to both the N-and C-lobes, and it is an essential, conserved feature of all AGC kinases, (Fig. 1A) (3). The turn motif and HM sites wrap around the N-lobe and position it for catalysis (3,4).…”
mentioning
confidence: 99%
“…A small N-terminal lobe (N-lobe) and a larger carboxyl-terminal helical lobe (C-lobe) create a cleft between the two lobes where the ATP substrate binds. All EPKs have an activation loop in the C-lobe that typically harbors a conserved activation loop phosphorylation site, which is a major regulatory site (2)(3)(4). Other kinase-specific phosphorylation sites may be auto-or trans-phosphorylated by heterologous kinases.…”
mentioning
confidence: 99%